Prinsip Pembelajaran dalam Kurikulum Merdeka - Muhamad Damiati; Nurasikin Junaedi; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to explore and discuss the principles and ways of learning in the independent curriculum. whether the way of learning that we carry out is correct or in accordance with the Independent Curriculum or is it still with the old pattern, and the government changes the curriculum to the Merdeka curriculum, this is not just a project not just a name change but the government really wants to improve the education system in Indonesia according to the times and also the evaluation carried out by the government. In this study report, the method used is a descriptive qualitative method by taking notes because the source of the data obtained by listening to the oral narrative from the Young Teacher's Note Youtube channel entitled